Active contours for image segmentation using complex domain‐based approach. Issue 2 (1st February 2016) - Hussain, Sajid; Chun, Qi; Asif, Muhammad Rizwan; Khan, Muhammad Sohrab
Abstract : A complex domain‐based approach of active contour model has been proposed for image segmentation which deforms iteratively to partition an image into various useful regions. A new region‐based complex pressure force function has been designed which gives shape to the dynamic active contour using image forces, and efficiently control the propagation of moving interface. This model makes the level set function binary, uses Gaussian smoothing kernel to regulate and avoid re‐initialisation procedure. The working scheme of the model is as: the real image data is converted into complex data by iota ( i ) times and the average iota ( i ) times of horizontal and vertical components of gradient is inserted in the model to develop complete complex gradient. The proposed model can be implemented by simple finite difference scheme. The efficiency and robustness of the authors model have been verified.